Temporal patterns of diversification in Brassicaceae demonstrate decoupling of rate shifts and mesopolyploidization events - Huang, Xiao-Chen; German, Dmitry; Koch, Marcus (Annals of botany, 2020)
Abstract. Background and Aims: Whole-genome duplication (WGD) events are considered important driving forces of diversification. At least 11 out of 52 Brassicace tribes had independent mesopolyploid WGDs followed by diploidization processes. However, the association between mesopolyploidy and subsequent diversification is equivocal. Herein we show the results from a family-wide diversification analysis on Brassicaceae, and elaborate on the hypothesis that polyploidization per se is a fundamental driver in Brassicaceae evolution.